Synthesis, Structure, and Halo‐, Photo‐, and Thermochromism Properties of 5‐Azotriazolyl Salicylic Acid and Its CdII Complex. Issue 6 (13th May 2013) - Lin, Jiao‐Min; Yang, Meng; Qiu, Yan‐Xuan; Chen, Wen‐Bin; Yan, Hua; Gao, Fei‐Xian; OuYang, Zhen‐Jie; Dong, Wen; Kuang, Tong‐Chun
Abstract A hydrated 5‐azotriazolyl salicylic acid of [(H3ATSA)]⋅2 H2O (1) and its CdII complex of [Cd2(H2ATSA)4]⋅13 H2O (2) have been synthesized and characterized by single‐crystal X‐ray diffraction analysis and a neutral trans‐Z‐enol form of H3ATSA and another anionic trans‐E‐enol H2ATSA− isomer have been found in 1 and 2, respectively. The yellow crystal of 2 can be transformed in situ into red crystals in NaOH solution. The diffuse reflectance and photoluminescent spectra for the crystal powder samples and the aqueous solutions of 1 and 2 have been investigated. The DFT and TDDFT calculations at B3LYP/6–31G* level for 1 and B3LYP/Lanl2dz level for 2 have been used to demonstrate the characteristic absorption spectra and the trans‐enol to cis‐keto photo‐ and thermoisomeric reaction for the ATSA3− anion. The onion cell imaging taken by confocal laser scanning microscope was observed with 1 and 2 as fluorescent labels.